Enhanced Directional Light Extraction from Patterned Rare‐Earth Phosphor Films. Issue 2 (20th November 2020) - Cabello‐Olmo, Elena; Molet, Pau; Mihi, Agustín; Lozano, Gabriel; Míguez, Hernán
Abstract: The combination of light‐emitting diodes (LEDs) and rare earth (RE) phosphors as color‐converting layers comprises the basis of solid‐state lighting. Indeed, most LED lamps include a photoluminescent coating made of phosphor material, i.e., crystalline matrix suitably doped with RE elements, to produce white light from a blue or ultraviolet LED chip. Transparent phosphor‐based films constitute starting materials for new refined emitters that allow different photonic designs to be implemented. Among the different photonic strategies typically employed to tune or enhance emission, surface texturing has proved its versatility and feasibility in a wide range of materials and devices. However, most of the nanofabrication techniques cannot be applied to RE phosphors directly because of their chemical stability or because of their cost. The first monolithic patterned structure of down‐shifting nanophosphors with square arrays of nanoholes with different lattice parameters is reported in this study. It is shown that a low‐cost soft‐nanolithography procedure can be applied to red‐emitting nanophosphors (GdVO4 :Eu 3+ nanocrystals) to tune their emission properties, attaining a twofold directional enhancement of the emitted light at predesigned emission wavelengths in specific directions. Abstract : Color‐converting layers made of nanophosphors are nanoimprinted with 2D square arrays with soft‐lithography techniques. Surface texturing in phosphor thin films enables brighter emission by enhancing light extraction at targeted wavelengths and directions. The photonic approach opens novel routes in the field of solid‐state lighting with monolithic patterned transparent thin films.